PEMBANGUNAN SISTEM APLIKASI PURCHASE REQUEST PROJECT BERBASIS WEB: STUDI KASUS PADA PT GRAND KARTECT TBK - Muhammad Afifudin (CKI ON SPOT, 2016)
In the age of technology that has been developed at this time, amid the rapid development of business throughout the world. Employers must keep up with technology in order to remain competent in business and continue to compete with its competitors in each respective field. Companies can operate like any other company if inside there are the production and operation. Production and operation of an activity creating goods and services that the company offers to consumers. There are obstacles in the course of the project with technological limitations connected computerized network for media booking needs of the project in the "trusted" in the ordering of project requirements in terms of materials and more time consuming. Then create a software system that aims to facilitate the process and streamline the processing time so that the implementation process of the production is still running and can be installed in the site can be implemented as time that has been set. Applications purchased request a Web-based project that can be accessed only with a set of computers with Internet netted. Design and development of aplication using the incremental method.